Solar energy in buildings thermal balance for efficient heating and cooling - Chwieduk, Dorota (Amsterdam Elsevier, 2014)
Solar Energy in Buildings presents solar radiation fundamentals and their applications in buildings, supported by theoretical analysis and results of original simulation studies in solar energy availability, collection, and conversion for both active and passive use. In-depth coverage of energy balance and heat transfer in building envelopes is supported by the inclusion of calculations and case studies, while contextualizing within an integrated design approach.--Provided by publisher.
Solar radiation - fundamentals -- Availability of solar radiation on the Earth -- Shaping building envelope with regard to incident solar radiation -- Photothermal conversion in a building -- Passive utilization of solar energy in a building -- Energy balance of a building with regard to solar radiation exposure -- Active solar systems in buildings -- Buildings "aware" of solar energy impact.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Building-integrated photovoltaic systems; Solar thermal energy; Solar buildings; Energy conservation; Electronic books